Study of Equilibrium and Kinetics of Ag(I) Metal Ions Adsorption on Carbon Nanofibers and Its Potential Test as X-Ray Anti-Radiation Material - L. O. Ahmad; W. O. A. Sulastri; Alimin; L. O. A. N. Ramadhan; H. Ritonga; Alwahab Alwahab; S. J. Sentosa; A. A. Umar (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2026)
X-ray radiation is an electromagnetic wave with short waves and has been widely used in the medical world, if excessive use can cause harm to the body. The purpose of this research are to know adsorption capacity and kinetics of CNFs adsorption to Ag (I) metal ion and its potential test as X-ray anti-radiation material. This research uses liquid phase adsorption method with the help of ultrasonic wave in the process of attaching metal ion Ag (I) with CNFs as adsorbent. The result, showed the optimum adsorption process at 60 minutes, pH 8 and concentration of 20 mg/L. Ag(I) metal ions on CNFs maximum adsorption capacity was 398.4064 mg/g, with the adsorption process followed pseudo second order adsorption kinetics model. XRD test results in decreasing intensity after attachment of Ag (I) ions on CNFs and the potentially serve as X-ray anti radiation material.